Environmental regulation, R&D subsidies, and industrial green total factor productivity - Bu Wei; Li Chenxi; Liu Shanshan (Sustainable Futures)
In the face of worsening global environmental degradation, significant attention has been devoted to the greening of industrial transformation and development, specifically by improving industrial green total factor productivity (GTFP). We explored the impact of environmental regulations on industrial GTFP and the moderating influence of R&D subsidies. We established a theoretical model in which environmental regulations affect industrial GTFP, and this relationship is moderated by R&D subsidies. The results revealed that the impact of environmental regulations on industrial GTFP is U-shaped and that the current level of environmental regulation is insufficient to boost industrial GTFP. Green technological innovation plays a mediating role in the effect of environmental regulations on industrial GTFP. Furthermore, R&D subsidies nonlinearly moderate the relationship, resulting in a steeper U-shaped curve and accelerating the arrival of the tipping point. These findings provide theoretical support and a reference for government policies that promote industrial greening.